Coir Pith for Eco-Development - Rohella, R.S.; Sahu, D.K.; Mahapatra, H. (Asian Journal of Chemistry, 2016)
Due to poor or non-utilization of coir pith all round the world, its accumulation in the coconut producing countries since the last century has created ecological imbalance and thus has been designated as an unwanted waste. The huge generation of coir pith over the years, therefore, has caused serious problems like shortage of space pollution of land, water and air, loss of soil fertility due to percolation of lignin in the soil, deforestation, soil erosion, etc. In the present paper, the physical and chemical properties of coir pith carried out by laboratories of Auburn and Arkansas Universities at United States laboratory have been presented. The recent reported use of coir pith in conjunction with coir in the field of horiticulture, agriculture as coil brick, coir block and agro manure have been discussed. Many more specific applications with innovative designs of above materials in erosion control, vine hops, geo-textile, packaging, chemical industry and as rolls, matting and twines, fire resistant fabrics, portable readymade lawns, etc., have paved the way for the large-scale utilization of coir and coir pith for revenue generation commodities. The results of investigations carried out for the characterization of coir pith and process for the extraction and purification of lignin from coir pith is expected to enhance the utilization and industrial applications of coir pith have also been presented.